BUSINESS PLAN CLINIC ESUMI HEMODIALYSIS OF SOCIAL SECURITY AGENCY (BPJS) IN TANGERANG CITY - Riady, Andrew; Nasrul, Anas; Widodo, Agus; Prabowo, Erlang Sigit; Anggraini, Susi (Jurnal Ekonomi : Journal of Economic, 2017)
Chronic renal failure is a disease with decreased kidney function that can not be maintain metabolism and fluid and electrolyte balance. Patients with this condition require hemodialysis action to be able to sustain life. Hemodialysis action requires considerable costs. According to data PERNEFRI patients with chronic renal failure in Indonesia the number is increasing every year. In 2014 the Indonesian government issued a national health insurance program (JKN) organized by the Social Security Agency (BPJS) health. Conditions such as this is an opportunity to open a hemodialysis clinic.Keywords: Hemodialysis, BPJS, business plan.Â